FAKTOR–FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN: UKURAN PERUSAHAAN SEBAGAI PEMODERASI - LILIS LISMAWATI; SURYANTO SURYANTO (Jurnal Bisnis dan Akuntansi, 2017)
The purpose of this study is to examine the factors affecting dividend policy on non-financial companies. The independent variables consist of return on equity, earnings per share, liquidity, current earnings, growth opportunity, institutional ownership, leverage. As for the moderation variables are firm size. Population of this research are non financials companies listed in Indonesia Stock Exchange from 2012-2015. The samples of this study are 280 data using purposive sampling method. This research uses multiple regression method for data analysis. The results of this study indicate that the current earnings and current earnings, variables that are moderated by the firm size have an influence on the dividend policy. Another independent variables such as return on equity, earnings per share, liquidity, growth opportunity, institutional ownership, leverage, and firm size have no effect on dividend policy.